Perceived social support and family members of patients with mental disorders: A mixed method study - Amini, Shabnam; Jalali, Amir; Jalali, Rostam (Frontiers in Public Health, 2023)
Introduction Family members are the caregivers to patients with mental disorders at home, and the mental and spiritual pressures caused by this responsibility necessitate physical, mental, and perceived social support for these families. The present mixed method study is an attempt to elaborate on the perceived social support by Iranian families of patients with chronic mental disorders. Materials and methods Using a sequential mixed method explanatory study (quantitative and qualitative), 200 family members of patients with chronic mental disorders were selected through convenient sampling (quantitative phase). Data gathering was started using a demographics form and Stewart and Sherburne's perceived social support scale. The qualitative phase included 10 participants who obtained low scores in the quantitative phase and took part in private, face-to-face, in-depth, and semi-structured interviews. The data obtained in the quantitative phase were analyzed using statistical tests, and the interviews were analyzed using qualitative content analysis. Findings The perceived social support by the participants was at a moderate level in different fields of tangible support, information and emotional support, kindness, and positive social interactions. The results of the qualitative phase revealed social support status in 15 subcategories, 6 categories, and 2 themes of support and acceptance by family, relatives, and friends, with support and being understood by society. The results of the qualitative and quantitative sections emphasized the needs of the patient's family members (who acted as caregivers for patients) for support in family, social, and emotional areas. Conclusion The family members of patients with chronic mental disorders have different needs in the area of perceived social support. Such needs are more tangible in family members such as children with mentally ill parents or parents with mentally ill children. The results of this study can be used for educational and supportive planning for caregivers of patients, most of whom are family members.